2012
DOI: 10.1371/journal.pone.0040779
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Rat Sensory Ganglia after Local Inflammation Implicates Novel Cytokines in Pain

Abstract: Inflammation plays a role in neuropathic pain conditions as well as in pain induced solely by an inflammatory stimulus. Robust mechanical hyperalgesia and allodynia can be induced by locally inflaming the L5 dorsal root ganglion (DRG) in rat. This model allows investigation of the contribution of inflammation per se to chronic pain conditions. Most previous microarray studies of DRG gene expression have investigated neuropathic pain models. To examine the role of inflammation, we used microarray methods to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 45 publications
4
48
0
Order By: Relevance
“…The concentration of active endogenous glucocorticoids can be locally regulated by the two forms of 11β-hydroxysteroid dehydrogenase: type 1 that reversibly forms these active corticosteroids from their 11-dehydroxy forms, and type 2 that inactivates them 16,22 . Both type 1 and type 2 enzymes were present in the DRG, and the type 1 was significantly upregulated 3 days after local DRG inflammation by microarray 42 . The activity of these enzymes also depends on the redox state of the cell, which may change with inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…The concentration of active endogenous glucocorticoids can be locally regulated by the two forms of 11β-hydroxysteroid dehydrogenase: type 1 that reversibly forms these active corticosteroids from their 11-dehydroxy forms, and type 2 that inactivates them 16,22 . Both type 1 and type 2 enzymes were present in the DRG, and the type 1 was significantly upregulated 3 days after local DRG inflammation by microarray 42 . The activity of these enzymes also depends on the redox state of the cell, which may change with inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, this Ca 2+ response was remarkably attenuated by a CXCR3 antagonist. The upregulated CXCL10/CXCR3 signaling within DRG was also observed in the context of inflammatory/neuropathic pain [1; 10; 43]. Two variants of CXCR3 (CXCR3-A and CXCR3-B) have been identified [40].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that both CXCL10 and CXCR3 are expressed in the nervous tissues [20; 31], including primary sensory neurons [1]. Moreover, CXCL10/CXCR3 signaling in sensory neurons was upregulated under inflammatory or neuropathic pain conditions and was implicated in the maintenance of a chronic pain state [1; 10; 43]. Our recent study showed that cutaneous primary sensory neurons innervating the CHS skin became more excitable [34].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, CXCL10 was upregulated in DRG neurons in rats after an experimentally induced inflammation of the ganglion (Strong et al 2012) or after a demyelination of the nerve (Bhangoo et al 2007) and was upregulated in DRG neurons from human after infection of the ganglion with varicellazoster virus (Steain et al 2011). It remains to be determined whether the activation of neurons expressing message or protein for CXC10 would release CXCL10 from DRG neurons.…”
Section: 5 Acd Upregulates Cxcr3 Chemokine Receptor Signaling In Cumentioning
confidence: 90%